Adsorption of neomycin from water using activated carbon from flax seeds - Patience Mapule Thabede; Ntaote David Shooto (South African Journal of Chemical Engineering)
New carbon-based flaxseed adsorbents were prepared for the efficient removal of an organic pollutant (neomycin) from an aqueous solution. In the study, the use of H3PO4 and NaOH-activated flax seeds was investigated and used for batch adsorption studies. The H3PO4 treated carbon adsorbed more than the NaOH carbon at about 53.68 and 45.85 mg/g, respectively. Effect of temperature showed that increasing the temperature decreased the sorption capacity of neomycin from 283<293<303 K. The equilibrium data for both adsorbents matched the Langmuir sorption isotherm, indicating that the uptake of neomycin occurred at sorption sites with equal affinity for the contaminant with the formation of a monolayer on the adsorbent surfaces. The rate of neomycin removal was faster and took place within 30 min for both adsorbents. Neomycin removal was faster with both adsorbents and took place within 30 min. The uptake of neomycin was high at a higher pH of the solution and maximum adsorption was achieved at a pH of 8. The PSOM described the sorption data better, suggesting that the uptake mechanism involves electrostatic interactions. Examination of the FTIR spectra before and after uptake showed that the positions of the active interactions between the neomycin and the adsorbents were functional groups (-COOH, -C-OH and -CH) on the surface of both adsorbents. Therefore, activated carbon from flax seed is a promising adsorbent for the uptake of organic pollutants such as neomycin from water.